2001
DOI: 10.1046/j.1540-8175.2001.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Contrast Echocardiography: A New Gold Standard for Perfusion Imaging?

Abstract: Recent developments have permitted myocardial contrast echocardiography (MCE) to become a new method of noninvasively assessing myocardial perfusion in humans. Preliminary studies of myocardial perfusion imaging during adenosine, dipyridamole, and dobutamine stress echocardiography have shown excellent agreement with either radionuclide uptake or quantitative angiography. This article reviews the recent advances in microbubble technology, ultrasound imaging, and myocardial physiology that have made contrast ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Myocardial contrast echocardiography (MCE) has recently emerged as a potentially useful method for studying myocardial perfusion in coronary artery disease and reperfusion after acute myocardial infarction 3–6 . Experimental studies based on animal models confirmed that MCE accurately delineated myocardium during coronary occlusion, as well as quantifying the ultimate size of an infarct 7 …”
mentioning
confidence: 99%
“…Myocardial contrast echocardiography (MCE) has recently emerged as a potentially useful method for studying myocardial perfusion in coronary artery disease and reperfusion after acute myocardial infarction 3–6 . Experimental studies based on animal models confirmed that MCE accurately delineated myocardium during coronary occlusion, as well as quantifying the ultimate size of an infarct 7 …”
mentioning
confidence: 99%